The Analysis of Human-Animal Bond as a Catalyst for Personal Transformation in a Street Cat Named Bob Novel - Tati Mardewi; Nurmala Dewi; Furi Indriyani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The research analyzes the effect of the human-animal transformation bond in the novel, A Street Cat Named Bob, written by James Bowen. This observes the effect of the human-animal bond to help psychological stabilization, reconstruction, and social reintegration. The Bowen’s story is placed in the form of contemporary recovery narratives. Research was conducted with qualitative thematic analysis approach based on attachment theory and recent human-animal bond research. The research comes from repeated close reading of the novel. The data were organized using a theory based on the concepts of caregiving system and moral awareness, emotional co-regulation, social interdependence and animals as social catalysts, and personal transformation and relational identity. There are results finding that are got from this research: (1) The cat is a bond figure that gives safety and emotional continuity; (2) caregiving and responsibility activate moral awareness encourages a behavior change; (3) the relationship between Bowen and the cat reduce anxiety and relapsing; (4) The bond changed the protagonist's internal working model, making him see himself positively; (5) the cat is a changeable social agent facilitate interaction and work opportunity (6) depending on each aspects grow an ethical relational identity and transforms the individual. This finding shows that a relational framework is crucial to seeing the social dimensions of an individual’s psychological transformation.